P001 Creating acceptable tablets (CAT) – a feasibility study to assess the swallowability and acceptability of different sized placebo tablets in children and young people: an interim analysis. Issue 7 (19th June 2019) - Bracken, Louise; McDonough, Emma; Wilson, Fiona; Ashleigh, Samantha; Ohia, Udeme; Mistry, Punam; Jones, Huw; Kanji, Nazim; Liu, Fang; Peak, Matthew
Abstract : Aim: To determine the feasibility of investigating the swallowability and acceptability of different sized placebo tablets in children and young people (CYP) aged 4–12 years and estimate consent/recruitment rates for a future study. Methods: Participants were asked to swallow three different sized placebo tablets; 6mm, 8mm and10mm in a standardised order, smallest to largest. The recruitment target is 50 children, including both healthy children and NHS inpatients/outpatients. Following informed consent participants were shown a short video demonstrating how a tablet can be swallowed. The researcher observed and recorded the child's facial expressions as they swallowed the tablet. 1 Any tablet chewing, signs of choking and/or coughing during and after swallowing were recorded. After each administration, an internal inspection of the mouth was conducted by the researcher to identify any residue or non-swallowed tablet. 2 The participants assessed the swallowability and acceptability of the samples using a questionnaire that included a 5-point hedonic facial scale and voluntary feedback was provided. Faces 1-3 on the hedonic scale were deemed acceptable to the participant. The process described above was repeated for swallowing the 8mm and 10mm tablets. Participants were offered all three different sized placebo tablets and were given the option to stop or continue at each stage. Children who successfully swallowed all three samples were asked if they would be willing to take part in the study again if the tablet administration order was randomised rather than in order of increasing size. Results: To date, 32 participants aged between 4-12 years have taken part in the study (mean age 7.7 years). Twelve children were aged 6 or under. All 32 participants attempted to swallow the 6mm tablet, 27 attempted the 8mm and 25 children attempted the 10mm tablet. 78.1% successfully swallowed the 6mm tablet and 85.2% successfully swallowed the 8mm and 10mm tablets. Participants were also asked about the most important factors when taking a tablet, data were available for 30/32 participants and the most important factor was deemed tablet size (17/30), followed by taste (7/30) responses. 87% of children who swallowed all three samples reported that they would be willing to take part in the study again if the tablet size order was randomised. Conclusion: The preliminary results show that tablets may be an acceptable dosage form for children from 4 years old. Tablet size was deemed to be the most important factor of swallowability/acceptability of tablets in children. The full data set should give further information about optimal tablet size for CYP which is currently unknown. This feasibility study will collate data on key variables which will inform the design of a larger, definitive study including the sample size based on observed recruitment/consent rates. References: Zeinstra GG, Koelen MA, Colindres D, et al. Facial expressions in school-aged children are a good indicator of 'dislikes', but not of 'likes'. Food Quality and Preference 2009 December;20(8):620–624. Klingmann V, Spomer N, Lerch C, et al. Favorable Acceptance of Mini-Tablets Compared with Syrup: A Randomized Controlled Trial in Infants and Preschool Children. The Journal of Pediatrics 2013 December;163(6):1728–1732.e1.